Citizen Journalism: Ketika Berita Tidak Hanya Memiliki Satu Muka - Zaki Habibi (Jurnal Komunikasi, 2007)
Journalism became a term that mass media had controlled the meaning for recent years. Audiences have no power to show their role in news production and dissemination. Now, when society face an information era, the power of knowledge and informations no longer lay-down only at newsroom or editors of mass media. Internet created many changes in the way people signify realities. Citizen journalism—as a new form of online journalism—offers a new paradigm and spirit which put individual as important subject in the process of social meaning construction.